Designing a cocktail containing redox enzymes to improve hemicellulosic hydrolysate fermentability by microorganisms - Tramontina, Robson; Brenelli, Lívia Beatriz; Sousa, Amanda; Alves, Rafael; Zetty Arenas, Ana Maria; Nascimento, Viviane Marcos; Rabelo, Sarita Cândida [UNESP]; Freitas, Sindélia; Ruller, Roberto [UNESP]; Squina, Fabio Marcio (Elsevier, 2020)
Bioproducts production using monomeric sugars derived from lignocellulosic biomass presents several challenges, such as to require a physicochemical pretreatment to improve its conversion yields. Hydrothermal lignocellulose pretreatment has several advantages and results in solid and liquid streams. The former is called hemicellulosic hydrolysate (HH), which contains inhibitory phenolic compounds and sugar degradation products that hinder microbial fermentation products from pentose sugars. Here, we developed and applied a novel enzyme process to detoxify HH. Initially, the design of experiments with different redox activities enzymes was carried out. The enzyme mixture containing the peroxidase (from Armoracia rusticana) together with superoxide dismutase (from Coptotermes gestroi) are the most effective to detoxify HH derived from sugarcane bagasse. Butanol fermentation by the bacteria Clostridium saccharoperbutylacetonicum and ethanol production by the yeast Scheffersomyces stipitis increased by 24.0× and 2.4×, respectively, relative to the untreated hemicellulosic hydrolysates. Detoxified HH was analyzed by chromatographic and spectrometric methods elucidating the mechanisms of phenolic compound modifications by enzymatic treatment. The enzyme mixture degraded and reduced the hydroxyphenyl- and feruloyl-derived units and polymerized the lignin fragments. This strategy uses biocatalysts under environmentally friendly conditions and could be applied in the fuel, food, and chemical industries.
Keywords: Enzymatic detoxification; Fermentation inhibitors; Hydrothermal pretreatment; Lignin modification; Sugarcane bagasse